Presence of Unusual Foramen in the Sternum – A Case Report - , T. Ramesh Rao; , Suresh R. Rao (Archives of Current Research International, 2017)
Presence of sternal foramen is a familiar variation of the sternum that brings the danger of fatal impediments like pneumothorax, damage to vital structures like pericardial and cardiac puncture during acupuncture. The present day autopsy population shows about 6.7% of bony defects in the sternum. When present it is seen in solitary and found in the body of the sternum, rarely multiply and may be found in the manubrium. Review of literature suggests that presence of unusual foramen in the sternum is found at the age of 8-years and also in the persons of old age. During routine visual inspection of the bone collection housed in the Department of Anatomy, in one of the sternum we observed the presence of sternal foramen and bifid xiphoid process. The sternal foramen was somewhat oval shaped measuring 6.75 mm × 5.55 mm, and was present in lower one third of the body of the sternum. The sternal foramen and the bifid xiphoid process when present will be usually asymptomatic. Sternal foramen can be misinterpreted sternal foramen can be misinterpreted as osteolytic lesion. Manifestation of sternum in close relation to the mediastinal structures, occurrence of sternal foramen makes the lung, heart and great vessels vulnerable while execution of invasive procedures like bone marrow aspiration, acupuncture leading to life threatening impediments such as pneumothorax and cardiac tamponade.